How a local active force modifies the structural properties of polymers. Issue 10 (24th February 2020) - Natali, Laura; Caprini, Lorenzo; Cecconi, Fabio
Abstract : We study the dynamics of a polymer, described as a variant of a Rouse chain, driven by an active terminal monomer (head). Abstract : We study the dynamics of a polymer, described as a variant of a Rouse chain, driven by an active terminal monomer (head). The local active force induces a transition from a globule-like to an elongated state, as revealed by the study of the end-to-end distance, the variance of which is analytically predicted under suitable approximations. The change in the relaxation times of the Rouse-modes produced by the local self-propulsion is consistent with the transition from globule to elongated conformations. Moreover, also the bond–bond spatial correlation for the chain head are affected by the self-propulsion and a gradient of over-stretched bonds along the chain is observed. We compare our numerical results both with the phenomenological stiff-polymer theory and several analytical predictions in the Rouse-chain approximation.